2015
DOI: 10.1371/journal.pone.0144144
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Tumor Growth Rate Measured by US in Preoperative Period and Long Term Disease Outcome in Breast Cancer Patients

Abstract: ObjectiveThe aim of our study was to evaluate the effect of tumor growth rate, calculated from tumor size measurements by US, on breast cancer patients’ outcome.Patients and MethodsBreast cancer patients who received at least two serial breast ultrasonographies (US) in our institution during preoperative period and were surgically treated between 2002 and 2010 were reviewed. Tumor growth rate was determined by specific growth rate (SGR) using the two time point tumor sizes by US.ResultsA total of 957 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
3
24
0
1
Order By: Relevance
“…An advanced histological grade and the Ki‐67 status were associated with a high proliferation rate of malignant breast tumors . In this study, we found that posterior echo enhancement and calcification were independent US features for predicting tumor proliferation.…”
Section: Discussionmentioning
confidence: 49%
“…An advanced histological grade and the Ki‐67 status were associated with a high proliferation rate of malignant breast tumors . In this study, we found that posterior echo enhancement and calcification were independent US features for predicting tumor proliferation.…”
Section: Discussionmentioning
confidence: 49%
“…We speculate that the reduced rate may be due to the fact that the cells are embedded in the gel and that they must divide in a ''real 3D'' context. Of note, while very heterogeneous, the estimated breast tumor doubling times in vivo in patients are on the order of tens or hundreds of days (Heuser et al, 1979;Yoo et al, 2015).…”
Section: Direct Visualization Of Trastuzumab Effects On the Her2 + Tumentioning
confidence: 99%
“…This study has some limitations. In this study, the observation period of patients undergoing surgery was short, and the majority of patients had only two serial measurements, which could have led to imprecise calculations of DR; however, TV-DR has been reported to correlate with prognostic factors and disease-free survival in breast cancer at short observation periods [ 20 ]. Patients with an observation period of ≥3 months were enrolled to improve evaluation accuracy.…”
Section: Discussionmentioning
confidence: 99%